1980
DOI: 10.1002/jcp.1041030221
|View full text |Cite
|
Sign up to set email alerts
|

Self‐maintenance capacity of CFU‐S

Abstract: The numbers of CFU-S which developed in spleen colonies were measured 11 days after injection of irradiated mice with marrow from normal mice or mice which had been treated in one of a variety of ways. The broad spread of CFU-S numbers, seen by other authors, in colonies derived from normal marrow was confirmed. However, the range and distribution of CFU-S per colony was generally different in colonies derived from the marrow of mice which were recovering or had recovered from some form of depopulation. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…MRA cells therefore meet the criteria for genuine pre-CFU-S. Accepting the existance of a pre-CFU-S, it is plausible that the amply reported differences in selfrenewal capacity of CFU-S (Worton et al, 1969;Schofield and Lajtha, 1973;Micklem et al, 1975;Rosendaal et al, 1976Rosendaal et al, , 1979Hellman et al, 1978;Hodgson and Bradley, 1979;Schofield et a]., 1980;Johnson and Nicola, 1984;Mulder and Visser, 1987) should be explained at least partly by assuming various admixtures of pre-CFU-S in the cell populations studied. In addition, the previously proposed mechanisms of CFU-S self-renewal and differentiation need reappraisal.…”
Section: Discussionmentioning
confidence: 95%
“…MRA cells therefore meet the criteria for genuine pre-CFU-S. Accepting the existance of a pre-CFU-S, it is plausible that the amply reported differences in selfrenewal capacity of CFU-S (Worton et al, 1969;Schofield and Lajtha, 1973;Micklem et al, 1975;Rosendaal et al, 1976Rosendaal et al, , 1979Hellman et al, 1978;Hodgson and Bradley, 1979;Schofield et a]., 1980;Johnson and Nicola, 1984;Mulder and Visser, 1987) should be explained at least partly by assuming various admixtures of pre-CFU-S in the cell populations studied. In addition, the previously proposed mechanisms of CFU-S self-renewal and differentiation need reappraisal.…”
Section: Discussionmentioning
confidence: 95%
“…53 We have previously shown significant in vivo protection of day 12 CFU-S against the toxic effects of the methylating agent temozolomide, in combination with O 6 -beG, following reconstitution of mice with bone marrow which had been induced to express hATPA/GA as a result of retroviral gene transfer. 49 In the present study, we have investigated the ability of hATPA/GA expression to provide protection against BCNU, which has been used in a number of preclinical studies by other workers and is a potential agent for use in a clinical trial of ATase-mediated myeloprotection.…”
Section: Discussionmentioning
confidence: 99%
“…The day 12 CFU-S, under certain conditions of transplantation, can exhibit long-term repopulating ability despite their relatively low self-maintenance capacity. 53,54 Thus, while most day 12 CFU-S have only a transient reconstitution potential, 53,54 they are nonetheless somewhat characteristic of the multipotent cells that represent the ideal target for genetic chemoprotection. These studies showed a reduction in toxicity even in the presence of O 6 -beG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using 3 H-thymidine labelling and CFU-S assay explored the kinetics of growth of haemopoietic progenitors (Testa & Lord, 1973;Schofield et al, 1980). In prior studies we found that the doubling time of haemopoietic progenitors can be modulated by growth factors, determined by monitoring the proliferative kinetics of haemopoietic progenitors during the early phase of an in vitro clonal assay (Tanaka et al, 1995;Ohishi et al, 1996).…”
mentioning
confidence: 99%